(untitled) (REGE Revista de Gestão, 2024)
Purpose – This paper intends to verify the extent to which Clean Development Mechanism (CDM) projects intend to contribute to sustainable development (SD) in Brazil, one of the top three leading countries in terms of the number of CDM projects. The authors assess the impact of CDMs not only in environmental aspects, but also social and economic ones. Design/methodology/approach – The authors define a set of qualitative sustainability indicators and scrutinize documents regarding a sample of almost half of all the projects registered in Brazil between 2004 and 2020 (219 projects). Findings – The findings of this study contradict many previous studies finding very limited evidence of SD in CDMs in many different countries: most projects in Brazil intend to contribute to some extent with SD, with 91% and 75% claiming to improve social and economic aspects, respectively. Practical implications – The authors derive lessons from Brazil that can be used in other researches. Social implications – The authors derive lessons from Brazil and propose paths for public policy toward encouraging sustainable development. Originality/value – The empirical data set relies on data collected directly from each of the projects in Brazil (roughly half of all of them) between 2004 and 2020. This is not only up to date, but pushes further the analytical scope of previous works.